ASSESSMENT OF CREDIT AND FARM INPUT UTILIZATION AMONG RICE FARMING HOUSEHOLDS IN NIGER STATE NIGERIA - O. L. Abdulrahman; J. O. Ifabiyi; O. S. Salami; O. G. Bello; A. A. Abdulrahman (مجلة الأنبار للعلوم الزراعية, 2025)
This study assessed credit loan accessibility and its utilization among rice farming households in Niger State, Nigeria. A three-stage random sampling procedure was used to select a total of 160 rice farmers. A structured questionnaire was designed and administered to the sampled farmers. Data collected were analysed with frequency count, percentages, mean, standard deviation, Pearson Product Moment Correlation, and Chi-Square.  The findings showed that personal savings (mean=2.66) were the most important source of credit/loans. The mean amount accessed was N 686,400.00 (USD 404). The primary input procured or farm operations performed with financial credits accessed were: hiring man labour or machinery such as tractors (61.9%) and procuring fertilizer (66.3%). The main constraint facing rice farmers was the inability to access credit (mean=1.88). The result showed that farm size (r=0.623, p<0.01), years of experience (r = 0.805, p<0.01), and level of education (χ2=15.078, p<0.05) were significantly related to loan utilization by farmers. This study recommends the importance of empowering the extension service providers on loan sources and acquisition methods for rice farmers as well as encouraging financial institutions to provide low-interest loans to farmers using less cumbersome application processes